Dynamic Simulation Analysis of the Start-up Process of Take-up Device of the Belt Conveyor - Li Dongmei; Zhao Shiming (Jixie chuandong)
The dynamic characteristic of the belt conveyor in the start-up operating condition is analyzed,the dynamic simulation analysis of the take-up device of the belt conveyor started by the styles of the combined cycloid,Nordell and equal acceleration and the optimization simulation analysis of the pulling force are carried out,the oversize and the undersize of local stress in the belt is prevented,so that the security and reliability of the belt conveyor can be ensured.